Prefetching and caching schemes for IoT data in hierarchical edge computing architecture. (24th February 2020) - Chen, Tzu-Jung; Sheu, Jang-Ping; Kuo, Yung Ching
With the growing number of the internet of things (IoTs) devices and mobile devices, the data traffic produced by these devices causes high network load, and these devices endure long access latencies to communicate with the cloud. The emergence of edge computing, caching and prefetching at the edge of the networks are promising solutions to these problems. Therefore, we propose caching and prefetching schemes for the internet of things data based on a four-tier hierarchical edge computing architecture, and our goal is to reduce data access latency. In our architecture, caches are deployed at 1st- and 2nd-tier edge nodes and the caching scheme is designed especially for the IoTs data. We analyse the relations of all users' access requests and prefetch popular data among all users to the cache based on the predictions of user preferences. The experimental results show that the proposed schemes can effectively reduce user access latencies.